2023
DOI: 10.1111/1750-3841.16478
|View full text |Cite
|
Sign up to set email alerts
|

Production of salad dressings via the use of economically prepared cellulose nanofiber from lime residue as a functional ingredient

Abstract: Production of cellulose nanofiber (CNF) via the use of a more economical and less energy‐intensive means is desirable. Once formed, it is necessary to determine whether or not the prepared CNF would be capable of forming a Pickering emulsion as in the case of traditionally prepared nanofiber. In the present study, oil‐in‐water emulsions, namely, salad dressings, with CNF as a functional ingredient, were prepared. Lime residue powder as the source of dietary fiber was subject to high‐shear homogenization to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Notably, 2P–3F exhibited the highest pseudoplasticity. Similarly, reported that the highest lime residue powder concentration in salad dressing showed the highest apparent viscosity with shear thinning behavior.…”
Section: Resultsmentioning
confidence: 87%
“…Notably, 2P–3F exhibited the highest pseudoplasticity. Similarly, reported that the highest lime residue powder concentration in salad dressing showed the highest apparent viscosity with shear thinning behavior.…”
Section: Resultsmentioning
confidence: 87%
“…There are two primary forms of nanocellulose: cellulose nanocrystals (CNC) and cellulose nanofibers (CNF). Notably, it has been proposed as a stabiliser in a range of food products, including ice cream (Sun et al ., 2015; Velásquez‐Cock et al ., 2019; Yu et al ., 2021), sterilised coconut milk (Kunchitwaranont et al ., 2019), meat sausages (Qi et al ., 2020) and salad dressing (Hongho et al ., 2023). Furthermore, nanocellulose demonstrates its versatility by contributing to the production of fillings, crisps, chips, wafers, biscuits, creams, puddings, soups, and much more (Perumal et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These properties make NFC a suitable candidate for use as an emulsifier and a stabilizer, among other additives and ingredients. Use of NFC as a Pickering emulsifier has indeed been successfully tested in an array of food emulsions, including coconut milk (Kunchitwaranont et al., 2019), mayonnaise (Choublab & Winuprasith, 2018), and salad dressing (Hongho et al., 2023).…”
Section: Introductionmentioning
confidence: 99%